ACTOR PREPARATION FOR VIRTUAL PERFORMANCE: TECHNOLOGY’S ROLE IN CONTEMPORARY THEATRE PRAXIS - Basa, Murali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores Technology’s role in actor preparing methods for virtual performances. Virtual performances have gained popularity in recent years, and technology has played a substantial role in enabling actors to create more engaging and immersive performances. This paper outlines the various technologies used in virtual performances, including motion capture, virtual set design, and live streaming. The paper also discusses the challenges associated with technology’s use in virtual performances, such as technical difficulties, the lack of audience interaction, and the limitations of virtual set design. It highlights the importance of actors adapting their skills and techniques to suit virtual environments and production teams being aware of the technical requirements of virtual performances. The paper concludes that virtual performances offer a new and exciting way for performers to connect with audiences all over the world. By using technology technology in actor preparing methods for virtual performances has greatly enhanced the quality of virtual performances and has opened up new opportunities for actors and production teams. However, it is essential to recognize the challenges and limitations associated with technology’s use in virtual performances and to work towards finding solutions to overcome these challenges is essential.